O político nos filmes a novembrada e Cruz e Sousa, o poeta do desterro: uma análise discursiva - Giovanella, Lúcio Flávio (2010)
This study presents a discourse analysis of two films from Santa Catarina State, Brazil, one a feature-length film and the other a short film, viz.: A Novembrada, by Eduardo Paredes, and Cruz e Sousa, o poeta do Desterro, by Silvio Back. These are contemporary films, both based on constitutive elements of the Santa Catarina identity. A Novembrada relates to the political event of the same name, which took place during the military dictatorship on the occasion of a visit by General Figueiredo to the city of Florianópolis. The event was recorded by the local press, enabling the film to take those records as its basis in order to develop a fictional interpretation. Meanwhile, Cruz e Sousa, o poeta do Desterro, is based on the work of the Santa Catarina poet, to develop a fictional film interpretation of his work. The two films are exemplary of local film output, in which the political element is constitutive in various dimensions, not just in the subject matter, as in A Novembrada, but more importantly in how, specifically, the background record and the cinematographic material are worked in together in forms of interpretation that mobilize discursive memories. One manner of understanding that interweave, either by way of what is constructed or by way of what is preconstructed and silence, is made possible by the theory and method of discourse analysis, which results in a historical and ideological contextualization of this slice of Santa Catarina’s cinematography.